1999
DOI: 10.1149/1.1392584
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Sn and SnSb0.14 Powders for Lithium Storage Matrices in Lithium‐Ion Batteries

Abstract: Insertion of lithium into, or extraction from, metallic host materials can produce volume changes, which lead to rapid mechanical disintegration and deterioration of Li-alloy electrode performance. The cycling properties of Sn-based composite electrodes can be significantly improved by optimizing the morphology and microstructure of lithium storage matrices. Decreasing the particle size of the metallic host powders to a submicron scale and using an intermetallic multiphase structure are effective ways for main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(112 citation statements)
references
References 10 publications
5
107
0
Order By: Relevance
“…In recent years, researchers also use nanoscale materials to improve the electrochemical properties of the electrodes. As reported by Yang et al [18], the cycling stability of intermetallic anodes can be significantly improved by decreasing the particle size due to the reduction of volume changes and enhancement of Li-alloying kinetics. Previous researches have found that good cycling stability could be achieved in some nanoscale Sn-based intermetallic compounds [9,19].…”
Section: Introductionmentioning
confidence: 84%
“…In recent years, researchers also use nanoscale materials to improve the electrochemical properties of the electrodes. As reported by Yang et al [18], the cycling stability of intermetallic anodes can be significantly improved by decreasing the particle size due to the reduction of volume changes and enhancement of Li-alloying kinetics. Previous researches have found that good cycling stability could be achieved in some nanoscale Sn-based intermetallic compounds [9,19].…”
Section: Introductionmentioning
confidence: 84%
“…Yang et al [13] reported that some Sb-based materials with reduced particle size showed good cycling stability. They attributed the improvement of cycling * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The restoration of SnSb is beneficial in retarding the rate of agglomeration of SnSb particles into larger grains, which has been identified as one of the key reasons for poor cycle stability of Sn-based materials. [33,34] The reproducibility of the peaks in subsequent cycles strongly indicates excellent electrochemical reversibility of the SnSb-C composite.…”
Section: Resultsmentioning
confidence: 92%